Qualitative glance on total care in hospital infections - Nora Margarita Jacquier; Luisa dos Santos; Jorge Hugo Centeno (Rev Rene)
This article attempts to socialize thinking from the sociological point of view of an action research activity carried out in a Children’s Hospital in Posadas, Argentina. This phenomenon of Hospital Infections (HIs) was addressed through biomedical and sociological studies. This interdisciplinary approach provided understanding of social individual behavior as far as this issue is concerned. Care is multidimensional and has impacts on attention quality and population health. His are considered a serious public health issue; in general, they are brought about mainly due to health system mistakes. The hospital has been considered as a ‘total institution’, with a social order of its own. Ways of behavior are supported by conceptual assumption, beliefs and perceptions and also affect the way of constructing reality at everyday family care and health team levels. This disciplinary crossing favors the advance in the understanding of the social phenomena in relation to the complexity implied by health care